Tranexamic acid - cost effective method in preventing blood loss in total knee replacement - Sreehari, C. K.; ., S. Nithin; Shenoy, Mangesh; Shareef, A. J. (International Journal of Advances in Medicine, 2017)
Background: Total joint replacement is a frequently done procedure in modern day practice of any orthopedics unit. Limiting blood loss both postoperatively and intraoperatively presents a challenge to the surgeon. Use of tranexamic acid (TA) reduces perioperative blood loss and need for allogenic blood transfusion in patients undergoing total knee replacement. Methods: This is a randomized controlled study that involved 105 patients who underwent primary total knee arthroplasty at our institute. A total of 105 consecutive patients underwent total knee replacement (TKR) between 2009 and 2014 at our institute. No patients who had primary TKR were excluded from the study. The information was collected prospectively but reviewed retrospectively. Patients were allocated to either the TA group (TA, n = 55) or the control group (n = 50). Results: The results were analyzed and no significant differences between the groups were found in the demographic data. Our results demonstrate significant reduction in blood loss with the use of TA. Conclusions: We can conclude that TA use might be a good solution to the problem of massive allogenic transfusion requirements especially in developing countries. A meta-analysis which looked at double-blinded randomized controlled trial also found that TA was useful in reducing blood loss in major orthopedic procedures.